APPLICATION OF CONJUGAL VISIT IN THE INDONESIAN STATUTORY SYSTEM FOR CORRECTIONAL ASSISTED PERSONS - Heliany, Ina; Sihotang, Muhenri (The Islamic Education and Multiculturalism Foundation, 2022)
The problem of meeting the sexual needs or biological needs of prisoners is a problem that is often the cause of chaos in prisons. The non-channeling of these needs sometimes causes the inmate's emotions to become uncontrollable. In Indonesia, some provisions allow married prisoners to gather with their families through CMK (Family Visiting Leave) as stipulated in the Decree of the Minister of Justice of the Republic of Indonesia Number: M.01-PK.03.02 of 2001 concerning Family Visiting Leave for Prisoners. This regulation provides an opportunity for married inmates to go to their family's residence for 2 (two) days or 2 x 24 hours to allow the married prisoner to meet his sexual needs while taking time off. However, in practice, these regulations have yet to be maximized because this is often used by officers and has become a topic of discussion in the mass media. Various opinions and studies mention the need for prisoners to be given this right, one of which is the Conjugal Visit policy. Conjugal Visit is also often referred to as the